2012
DOI: 10.1096/fj.11-192732
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrous substrate geometry as a critical trigger for organization, self‐renewal, and differentiation of human embryonic stem cells within synthetic 3‐dimensional microenvironments

Abstract: Substrates used to culture human embryonic stem cells (hESCs) are typically 2-dimensional (2-D) in nature, with limited ability to recapitulate in vivo-like 3-dimensional (3-D) microenvironments. We examined critical determinants of hESC self-renewal in poly-d-lysine-pretreated synthetic polymer-based substrates with variable microgeometries, including planar 2-D films, macroporous 3-D sponges, and microfibrous 3-D fiber mats. Completely synthetic 2-D substrates and 3-D macroporous scaffolds failed to retain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 53 publications
1
38
1
Order By: Relevance
“…Several surfaces have been used for differentiation to specific cell types, such as cardiomyocytes (22,33,41), endothelial and bone cells (36), neurons (38,42), or definitive endoderm (38,43). Although polymers can be produced inexpensively, it can be difficult to characterize or control how these surfaces interact with cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several surfaces have been used for differentiation to specific cell types, such as cardiomyocytes (22,33,41), endothelial and bone cells (36), neurons (38,42), or definitive endoderm (38,43). Although polymers can be produced inexpensively, it can be difficult to characterize or control how these surfaces interact with cells.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then counterstained with Hoescht to identify osteogenic- and adipogenic-positive cells. Lysed samples were either used to determine ALP concentrations using an ALP activity assay per manufacturer’s instructions (QuantiChromTM), or the relative gene expression of ALP (Qiagen, ALP) or lipoprotein lipase (Qiagen, LPL), as previously reported 62 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, a 3-D porous natural polymer scaffold prepared from a chitosan and alginate complex was reported to sustain the self-renewal of human ESCs without the support of feeder cells or conditioned medium [82]. Similarly, Carlson et al [83] reported the combination of poly-D-lysine, which is a synthetic positively charged amino acid chain commonly used as a coating to enhance cell adhesion, with synthetic polymer scaffolds with a 3-D fibrous architecture promote the adhesion, proliferation, and self-renewal of human ESCs. Additionally, microcarrier particles have also been used as substrates to amplify various types of adherent cells [84].…”
Section: Synthetic Materialsmentioning
confidence: 98%